Regulatory interaction with the long-term insurance industry in pursuit of market stability and financial inclusion - Corne Heydenrych; John M. Luiz (South African Journal of Business Management, 2018)
This study explores how the financial regulator through interaction with the long-term insurance industry can give effect to greater market inclusion and financial stability. It follows a qualitative approach and we interview both industry representatives and the regulator. The results show that there is a possible tension between the regulatory objectives of market stability and financial inclusion and that an unbalanced focus on either objective could adversely affect the other. It suggests that the best way to ensure this balance is for industry, the regulator and government to coframe Issues, rather than being obliged to rely on the regulator to draft regulation in isolation. The entry level (base of the pyramid) insurance market may require a different paradigm to `usual' insurance constructs and this requires a more innovative approach from all stakeholders. The findings highlight strategic measures that may assist regulators in giving effect to greater market inclusion without prejudicing the stability of the market.
Keywords: 650